Feasibility study of transanal total mesorectal excision. Issue 6 (25th February 2013) - Velthuis, S.; van den Boezem, P. B.; van der Peet, D. L.; Cuesta, M. A.; Sietses, C.
<x xml:space="preserve">Abstract</x> Transanal TME a new option